Genome Wide Identification of Orthologous ZIP Genes Associated with Zinc and Iron Translocation in Setaria italica - Alagarasan, Ganesh; Dubey, Mahima; Aswathy, Kumar S.; Chandel, Girish (Frontiers in Plant Science, 2017)
Genes in the ZIP family encode transcripts to store and transport bivalent metal micronutrient, particularly iron (Fe) and or zinc (Zn). These transcripts are important for a variety of functions involved in the developmental and physiological processes in many plant species, including most, if not all, Poaceae plant species and the model species Arabidopsis. Here, we present the report of a genome wide investigation of orthologous ZIP genes in Setaria italica and the identification of 7 single copy genes. RT-PCR shows 4 of them could be used to increase the bio-availability of zinc and iron content in grains. Of 36 ZIP members, 25 genes have traces of signal peptide based sub-cellular localization, as compared to those of plant species studied previously, yet translocation of ions remains unclear. In silico analysis of gene structure and protein nature suggests that these two were preeminent in shaping the functional diversity of the ZIP gene family in S. italica. NAC, bZIP and bHLH are the predominant Fe and Zn responsive transcription factors present in SiZIP genes. Together, our results provide new insights into the signal peptide based/independent iron and zinc translocation in the plant system and allowed identification of ZIP genes that may be involved in the zinc and iron absorption from the soil, and thus transporting it to the cereal grain underlying high micronutrient accumulation.